Exploring the nutritional, pharmacological, and industrial potential of okra and its byproducts: a comprehensive review - Supriya Singh Gaur; Anusree Raveendran; A. Athulya; S. Adithya Narayanan; Rafeeya Shams; Kshirod Kumar Dash; Ayaz Mukarram Shaikh; Kovács Béla (Discover Food)
Abstract Okra (Abelmoschus esculentus) is a nutrient-rich and economically viable crop well known for its diverse benefits in the food and pharmaceutical industry. Besides okra fruit, its fresh leaves, flowers, and seeds are also rich in certain nutrients, including carbohydrates, protein, dietary fiber, vitamins, and minerals, significantly contributing to their beneficiary property. Moreover, okra intake provides several pharmacological benefits to the body, such as preventing chronic diseases like diabetes and hypertension due to bioactive compounds like flavonoids, polyphenols, and polysaccharides. Additionally, the diverse utilization of both okra and its byproducts in a variety of industries, such as food, textiles, pharmaceuticals, and packaging, has gained significant importance due to the use of okra pod mucilage as a natural thickening agent in food and biodegradable packaging material. Numerous health-aiding items, including protein supplements made from the fresh leaf of okra, herbal tea from the flower, and decaffeinated coffee made from the seeds, are also produced from okra and its byproducts. Further, it is easily available in sub-tropical and tropical parts of the world. Nonetheless, its potential is significantly overlooked in existing works. Owing to its potential and existing gaps, this review brings together several innovative aspects, including a detailed analysis of the nutrient profile, potential health benefits, bioactive composition, and the application of edible parts of okra. In addition, the role of okra and its byproducts in medicine, packaging, and food industries has been explored. This review also aims to highlight environmentally friendly products like biodegradable packaging and healthy products like coffee substitutes, herbal drinks, and low-calorie products from okra and its derivatives.